The state of local infrastructure investment in Europe - McGoldrick, Peter (European Investment Bank, 2021)
Europe's COVID-19 recovery strategy calls for large-scale public investment to "building back better." Municipalities account for 45% of all public investment - which makes them a key partner in recovery efforts. As poles of social and economic activities, municipalities will also be critical to addressing climate change and to improving digitalisation. Our municipality report analysis the findings of a survey of 685 municipalities conducted in the summer of 2020. We look at the types of projects municipalities are prioritising and which areas they think need more investment. We also analyse their ability to secure funding for key projects. In addition, the report provides important insights into regional investment gaps and the effect the pandemic had on investment priorities.